Bevacizumab for neovascular age related macular degeneration (ABC Trial): multicentre randomised double masked study. (10th June 2010) - Tufail, Adnan; Patel, Praveen J; Egan, Catherine; Hykin, Philip; da Cruz, Lyndon; Gregor, Zdenek; Dowler, Jonathan; Majid, Mohammed A; Bailey, Clare; Mohamed, Quresh; Johnston, Robert; Bunce, Catey; et al.
Abstract : Objectives To evaluate the efficacy and safety of intravitreous bevacizumab injections for the treatment of neovascular age related macular degeneration. Design Prospective, double masked, multicentre, randomised controlled trial. Setting Three ophthalmology centres in the United Kingdom. Participants 131 patients (mean age 81) with wet age related macular degeneration randomised 1:1 to intervention or control. Interventions Intravitreous bevacizumab (1.25 mg, three loading injections at six week intervals followed by further treatment if required at six week intervals) or standard treatment available at the start of the trial (photodynamic treatment with verteporfin for predominantly classic type neovascular age related macular degeneration, or intravitreal pegaptanib or sham treatment for occult or minimally classic type neovascular age related macular degeneration). Main outcome measures Primary outcome: proportion of patients gaining ≥15 letters of visual acuity at one year (54 weeks). Secondary outcomes: proportion of patients with stable vision and mean change in visual acuity. Results Of the 131 patients enrolled in the trial, five patients did not complete the study because of adverse events, loss to follow-up, or death. In the bevacizumab group, 21 (32%) patients gained 15 or more letters from baseline visual acuity compared with two (3%) in the standard care group (P<0.001); the estimated adjusted odds ratio was 18.1 (95% confidence interval 3.6 to 91.2) and the number needed to treat was 4 (3 to 6). In addition, the proportion of patients who lost fewer than 15 letters of visual acuity from baseline was significantly greater among those receiving bevacizumab treatment (91% (59) v 67% (44) in standard care group; P<0.001). Mean visual acuity increased by 7.0 letters in the bevacizumab group with a median of seven injections compared with a decrease of 9.4 letters in the standard care group (P<0.001), and the initial improvement at week 18 (plus 6.6 letters) was sustained to week 54. Among 65 patients treated with bevacizumab, there were no cases of endophthalmitis or serious uveitis related to the intervention. All end points with respect to visual acuity in the study eye at 54 weeks favoured bevacizumab treatment over standard care. Conclusions Bevacizumab 1.25 mg intavitreous injections given as part of a six weekly variable retreatment regimen is superior to standard care (pegaptanib sodium, verteporfin, sham), with low rates of serious ocular adverse events. Treatment improved visual acuity on average at 54 weeks. Trial registration number Current controlled trials ISRCTN83325075